2007
DOI: 10.1584/jpestics.g06-48
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of dieldrin concentration in cucumber fruits using Cucurbita rootstocks and activated carbon

Abstract: Dieldrin uptake by cucumber fruits was examined using a variety of cucumber scions and squash rootstocks. The effect of activated carbon on reducing uptake was also determined. Three varieties of cucumber (Cucumis sativus L.; Sharp 1, Natsusuzumi and Nankyoku 2) and three varieties of squash (Cucurbita spp.; Kirameki, Yuyuikkiblack and Shintosa) were used. There was no significant difference in dieldrin uptake between cucumber scion varieties. The order of uptake between the varieties of rootstock was Shintosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Inputs of amorphous carbons (Guo et al 1991; Martinez-iñ igo and Almendros 1992; Sluszny et al 1999) and condensed carbons (Guo et al 1991) have been demonstrated to increase the capacity of soils to absorb pesticides. Furthermore, AC has been found to reduce dieldrin uptake by cucumber (Hilber et al 2009;Hashimoto 2007) and heptachlor epoxide uptake by pumpkin (Murano et al 2009). However, AC is usually more expensive than biochars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inputs of amorphous carbons (Guo et al 1991; Martinez-iñ igo and Almendros 1992; Sluszny et al 1999) and condensed carbons (Guo et al 1991) have been demonstrated to increase the capacity of soils to absorb pesticides. Furthermore, AC has been found to reduce dieldrin uptake by cucumber (Hilber et al 2009;Hashimoto 2007) and heptachlor epoxide uptake by pumpkin (Murano et al 2009). However, AC is usually more expensive than biochars.…”
Section: Discussionmentioning
confidence: 99%
“…Further, some reports have suggested that activated carbons (ACs) are effective in suppressing dieldrin uptake by cucumber (Hashimoto 2007;Hilber et al 2009). Cucumber farmers consider that AC is relatively expensive compared with those of biochar such as wood chip charcoal.…”
Section: Introductionmentioning
confidence: 99%
“…30) Therefore, the effectiveness of pesticide reduction in crops cultivated in pots by setting long SAPs may also be lower than that in fields. Hashimoto et al 4) reported that application of activated carbon to fields reduced dieldrin concentrations in cucumber fruits to 42-64% of those cultivated in non-treated fields. The effectiveness of dieldrin reduction in cucumber fruits by applying activated carbon roughly corresponds to the results obtained in the present study by setting long SAPs.…”
Section: Influence Of Soil-aging Periods (Saps) On Pesticide Concentrmentioning
confidence: 99%
“…Recent studies of crops contaminated by persistent organic pollutants (POPs), including dieldrin and heptachlor exo-epoxide, showed that application of carbonaceous adsorbents, such as activated carbon, to soils [4][5][6] and a grafting technique using a low-uptake rootstock 4,7) effectively decreased concentrations of POPs in cucurbit crops. However, the pesticides on the market are more degradable than POPs in soils.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12] Dieldrin detected from cucumber was supposed to have come from soil contaminated in the past. 17) After implementation of the Positive List System, low level residues supposed to be drifts from other crops exceeded the MRL or uniform limit. Table 6 lists pesticide residues suggestive of unregistered application.…”
Section: Non-acceptable Residuesmentioning
confidence: 99%